Performance of a validated spontaneous preterm delivery predictor in South Asian and Sub-Saharan African women: a nested case control study. (12th December 2022) - Khanam, Rasheda; Fleischer, Tracey C.; Boghossian, Nansi S.; Nisar, Imran; Dhingra, Usha; Rahman, Sayedur; Fox, Angela C.; Ilyas, Muhammad; Dutta, Arup; Naher, Nurun; Polpitiya, Ashoka D.; Mehmood, Usma; et al.
Abstract: Objectives: To address the disproportionate burden of preterm birth (PTB) in low- and middle-income countries, this study aimed to (1) verify the performance of the United States-validated spontaneous PTB (sPTB) predictor, comprised of the IBP4/SHBG protein ratio, in subjects from Bangladesh, Pakistan and Tanzania enrolled in the Alliance for Maternal and Newborn Health Improvement (AMANHI) biorepository study, and (2) discover biomarkers that improve performance of IBP4/SHBG in the AMANHI cohort. Study design: The performance of the IBP4/SHBG biomarker was first evaluated in a nested case control validation study, then utilized in a follow-on discovery study performed on the same samples. Levels of serum proteins were measured by targeted mass spectrometry. Differences between the AMANHI and U.S. cohorts were adjusted using body mass index (BMI) and gestational age (GA) at blood draw as covariates. Prediction of sPTB < 37 weeks and < 34 weeks was assessed by area under the receiver operator curve (AUC). In the discovery phase, an artificial intelligence method selected additional protein biomarkers complementary to IBP4/SHBG in the AMANHI cohort. Results: The IBP4/SHBG biomarker significantly predicted sPTB < 37 weeks ( n = 88 vs. 171 terms ≥ 37 weeks) after adjusting for BMI and GA at blood draw (AUC= 0.64, 95% CI: 0.57–0.71, p < .001). Performance was similar for sPTB < 34 weeks ( n = 17 vs. 184 ≥ 34 weeks): AUC = 0.66, 95% CI: 0.51–0.82, p = .012. The discovery phase of the study showed that the addition of endoglin, prolactin, and tetranectin to the above model resulted in the prediction of sPTB < 37 with an AUC= 0.72 (95% CI: 0.66–0.79, p -value < .001) and prediction of sPTB < 34 with an AUC of 0.78 (95% CI: 0.67–0.90, p < .001). Conclusion: A protein biomarker pair developed in the U.S. may have broader application in diverse non-U.S. populations.